Formulasi Pembuatan Kerupuk Karak Dengan Penambahan Sodium Tripolyphosphate (Stpp) - ASTIKA, MONA; , Fitriana Mustikaningrum, S.Gz, M.Sc; , Eni Purwani, S.Si., M.Si (2015)
Background: Crackers karak is a dry product made from rice and Bleng or borax. Borax including hazardous and prohibited for use in the manufacture of food, so as to replace the use of STPP allowed borax and safer. STPP (Sodium Tripolyphosphate) is a food additive in the manufacture of crackers karak. STPP is used as a binder in water so that the water in the dough is not easily evaporate quickly so that the surface of the dough does not dry out and harden. Purpose: The purpose of this study was to determine the effect of STPP (Sodium Tripolyphosphate) to the level of development and acceptance of crackers karak. Methods: The study design used was a completely randomized design with different addition of Sodium tripolyphosphate (STPP) which is 0.1%, 0.3%, 0.5%. Expansion rate was measured by comparing the height of crackers karak before and after frying, the acceptance of crackers karak by trained panelists. Furthermore, the data were analyzed using statistical test One Way Anova with keperayaan rate of 95% and then continued DMRT Test (Duncan Multiple Range Test). Results: The results showed that the level of development crackers karak influenced by the addition of STPP. STPP addition of 0.1% showed the highest level of development that is 26.89%. Crackers karak denganb addition of 0.1% STPP is the most preferred coral crackers. Conclusion: All in all there was no effect of the addition of STPP and acceptance on crackers karak. Suggestions: Need to use comparison control to compare karak crackers with STPP and borax.